KOLABORASI AGAMA DAN BUDAYA UNTUK MENGUATKAN PERSATUAN INDONESIA - David, Abadi; Darmanto (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2025)
This paper attempts to review the collaboration between religion and culture. Religion and culture are two distinct entities. They can complement each other. Religion and culture must align to create unity and cohesion in this nation. This paper discusses the integration that occurs between religion and culture and their collaboration to achieve unity in accordance with the third principle of Pancasila. The method of data collection in this paper is a literature study. The sources of data for this paper include books, journals, and other relevant literature. This paper presents several facts showing that religion and culture collaborate to strengthen each other. Religion aligns with culture, and vice versa; culture aligns with religion. This is evidenced by the adaptation between religion and culture in the Indonesian archipelago